Understanding and unlocking the potential of graphene oxide nanosheets as antibacterial agents - Karahan, H. Enis (Nanyang Technological University, 2018)
Past research revealed the antibacterial behavior of nanocarbons. However, the mechanisms of nanocarbons’ bacterial inhibition actions are not entirely clear, and both the toxicity concerns and performance issues remain. This thesis tackles these problems systematically, focusing on the graphene oxide (GO), likely the most promising nanocarbon currently being researched for antibacterial applications. Since the influence of physicochemical properties of GO has been previously studied intensively, this thesis focuses on the other two important players in GO-bacteria interactions: i) environmental abiotic factors (“the surrounding”), and ii) biotic factors (specifically, the role of bacterial physiology). As the first step, I demonstrate that the antibacterial efficacy of GO greatly depends on the environmental salinity. Under low salinity conditions, GO inhibited the bacterial cells more effectively thanks to the hypoosmotic stress. Also interestingly, a polymeric stabilizer, Pluronic, reduced the fibroblast toxicity of GO while it boosted the bacterial inhibition efficacy of GO against Gram-negative bacteria. However, the combination of hypoosmotic stress and Pluronic-GO exhibited considerably less activity on a model Gram-positive pathogen, suggesting the crucial role of bacterial envelope thickness in bacterial survival. In relation, I have explored the GO susceptibility of bacteria harvested at exponential, stationary, and decline growth phases. The cells harvested at stationary growth phase were less susceptible against GO. Therefore, I have also tested if Pluronic-GO mixture inhibits stationary-phase bacteria and observed its failure. Eventually, complementing GO with simple alcohols at low concentration, I have introduced a new method that dramatically enhances the antibacterial activity of GO against stationary-phase bacteria as well.